The 2018 public consultation on standardized packaging in Singapore: Analysis of policy actors' submissions - Amul, Gianna Gayle Herrera (Frontiers in Political Science, 2022)
After a public consultation in 2018, Singapore implemented standardized tobacco packaging as part of its portfolio of tobacco control policies in 2020, in compliance with Article 11 guidelines for implementing the World Health Organization Framework Convention on Tobacco Control. This study analyzed policy actors in opposition to standardized packaging in Singapore and their submissions to the public consultation. Policy actors were profiled, and their arguments were then coded and compared across submissions. Descriptive results were then summarized in a narrative synthesis. In total, 79 submissions were considered for final analysis that opposed plain packaging in Singapore. Thematic analysis shows that transnational tobacco companies and their subsidiaries in Singapore, along with a variety of policy actors opposed to the standardized packaging policy, have significant similarities in arguments, often with identical statements. Industry tactics included framing tobacco as a trade and investment issue; utilizing trade barriers, intellectual property, and investment rights; pursuing litigation or threat of litigation; mobilizing third-party support and citing policy failure. This study provides evidence that further contributes to the growing literature on commercial determinants of health particularly industry tactics and, in this case, where the tobacco industry and its local and global allies, utilize to counter evidence-based tobacco control measures.